Preliminary design and development of dry wear tester-pin on disc jigs - Raja Mohd Noor Azhar Raja Nordin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Polishing and Grinding process are the improtant process in the Powder Metallurgy. The purposes of this test are to study about the wear rate, mass of material removal rate and the character of the material that used. Due to the currently problem that facing by students, the force applied to the specimen is not uniformly exerted. Other than that, the current wear test machine tent to vibrate that can affected the experiment result. This is because the current machine still using the human force to hold the specimen in the disc surface. Due to this problem, a special jig has been desinged, developed and proposed. The analysis prove that the jig has been develop have good results of an engeneering strengthens and durability.Finally, there is significant of developing a new jig in a wear tester-pin on disc machine.